A Review of Reagents for Fluorescence Microscopy of Cellular Compartments and Structures, Part I: BacMam Labeling and Reagents for Vesicular Structures. Issue 1 (1st July 2013) - Dolman, Nick J.; Kilgore, Jason A.; Davidson, Michael W.
Abstract: Fluorescent labeling of vesicular structures in cultured cells, particularly for live cells, can be challenging for a number of reasons. The first challenge is to identify a reagent that will be specific enough where some structures have a number of potential reagents and others very few options. The emergence of BacMam constructs has allowed more easy‐to‐use choices. Presented here is a discussion of BacMam constructs as well as a review of commercially‐available reagents for labeling vesicular structures in cells, including endosomes, peroxisomes, lysosomes, and autophagosomes, complete with a featured reagent for each structure, recommended protocol, troubleshooting guide, and example image. Curr. Protoc. Cytom . 65:12.30.1‐12.30.27. © 2013 by John Wiley & Sons, Inc.